Weather - Maynard, Marc; MMStudios (Tulsa, OK : EDC, 2008)
Contains color illustrations of scenes from each of the four seasons, with labeled pictures of objects for young readers to find.
Cover title.
On tabbed board pages.
Spine title: Look and say weather.
K-3
Keywords: Seasons -- Juvenile literature; Vocabulary -- Juvenile literature; Weather -- Juvenile literature; Seasons; Vocabulary; Weather; Seasons; Vocabulary; Weather